2018
DOI: 10.7554/elife.37881
|View full text |Cite
|
Sign up to set email alerts
|

Par3 interacts with Prickle3 to generate apical PCP complexes in the vertebrate neural plate

Abstract: Vertebrate neural tube formation depends on the coordinated orientation of cells in the tissue known as planar cell polarity (PCP). In the Xenopus neural plate, PCP is marked by the enrichment of the conserved proteins Prickle3 and Vangl2 at anterior cell boundaries. Here we show that the apical determinant Par3 is also planar polarized in the neuroepithelium, suggesting a role for Par3 in PCP. Consistent with this hypothesis, interference with Par3 activity inhibited asymmetric distribution of PCP junctional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 91 publications
(150 reference statements)
2
26
0
Order By: Relevance
“…In addition, assessment for specificity by a rescue strategy of the Par3MO is not possible because expression of Par3 alone also leads to apicobasal defects (Afonso and Henrique, 2006). The mild effects observed after Par3MO electroporation are in line with Par3 lossof-function data published elsewhere (Chuykin et al, 2018), suggesting that the knockdown is efficient; however, readers may decide to ignore these data due to the lack of formal validation of Par3MO.…”
Section: Overexpression Of Mmp14 Is Sufficient To Promote Basal Mitosmentioning
confidence: 81%
“…In addition, assessment for specificity by a rescue strategy of the Par3MO is not possible because expression of Par3 alone also leads to apicobasal defects (Afonso and Henrique, 2006). The mild effects observed after Par3MO electroporation are in line with Par3 lossof-function data published elsewhere (Chuykin et al, 2018), suggesting that the knockdown is efficient; however, readers may decide to ignore these data due to the lack of formal validation of Par3MO.…”
Section: Overexpression Of Mmp14 Is Sufficient To Promote Basal Mitosmentioning
confidence: 81%
“…During mouse inner ear development, Par3 is asymmetrically localized in dependence on canonical PCP and Rac signaling but independently of Par6 and aPKC, moreover, it does not control spindle positioning through LGN/Gαi (Landin Malt et al, 2019). Interestingly, it has also been recently shown that Par3 might have an instructive role in PCP by direct binding to the core canonical PCP component Prickle3 during establishment of PCP in the Xenopus neural plate (Chuykin et al, 2018). On the other hand, Par3-dependent apicobasal polarity seems to be required to set up PCP in avian embryos (Lin and Yue, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated, "active" myosin-II is primarily localised to these cell borders. A large body of work in Xenopus demonstrates that the apical determinant Par3 physically associates with PCP components to localise them at the apical surface 80 where they reside preferentially at contractile cell-cell junctions 81 .…”
Section: Discussionmentioning
confidence: 99%